Experimental investigation of pyrolysis of rice straw using bench-scale auger, batch and fluidized bed reactors. (15th December 2015) - Nam, Hyungseok; Capareda, Sergio C.; Ashwath, Nanjappa; Kongkasawan, Jinjuta
Abstract: Energy conversion efficiencies of three pyrolysis reactors (bench-scale auger, batch, and fluidized bed) were investigated using rice straw as the feedstock at a temperature of 500 °C. The highest bio-oil yield of 43% was obtained from the fluidized bed reactor, while the maximum bio-char yield of 48% was obtained from the batch reactor. Similar bio-oil yields were obtained from the auger and batch type reactors. The GCMS and FTIR were used to evaluate the liquid products from all reactors. The best quality bio-oil and bio-char from the batch reactor was determined to have a heating value of 31 MJ/kg and 19 MJ/kg, respectively. The highest alkali mineral was found in the bio-char produced from the auger reactor. The energy conversion efficiencies of the three reactors indicated that the majority of the energy (50–64%) was in the bio-char products from the auger and batch reactors, while the bio-oil from the fluidized bed reactor contained the highest energy (47%). A Sankey diagram has been produced to show the flows of product energy from each pyrolysis process. The result will help determine which conversion process would be optimal for producing specific products of bio-char, bio-oil, and gas depending on the needs. Highlights: Pyrolysis products from auger, batch, and fluidized bed reactor were examined. O/C ratios of bio-oils stayed in specific ranges depending on the process reactors. The largest quantity of bio-oil from fluidized, while the best quality from batch. The highest alkali concentration of 37 g/kg included in the auger based bio-char. Sankey diagram was used to understand the energy distribution from reactors.